AKTIVITAS INHIBITOR Α-AMILASE ISOLAT KHAMIR ENDOFIT DARI TUMBUHAN BROTOWALI (Tinospora crispa L.) - Pramita Dian Pramitasari; Sri Pujiyanto; Agung Suprihadi (Jurnal Akademika Biologi, 2017)
Diabetes mellitus is a carbohydrate, fat, and protein metabolism disorder characterized by high blood sugar level. The α-amylase inhibitor may inhibit the carbohydrates digestion and cause a rate decrease of glucose absorption. The α-amylase inhibitors are found in a plant that potentially containing antidiabetic compounds, such as Brotowali (Tinospora crispa L.). The exploration of endophytic microbial is expected can produce secondary metabolites with similar properties to those produced by host plant metabolites. The purpose of this research were to obtain endophytic yeast isolates which can produce the best α-amylase inhibitors and to determine the ability of selected isolates to produce α-amylase inhibitors on varied carbon source and pH production media. This research was conducted by isolating endophytic yeast from roots, stems, and leaves of brotowali. The best isolate was selected by considering its inhibitory activity. The α-amylase inhibitor test was determined by measuring the resulting reduction sugar. This research used Completely Randomised Design. First treatment was carbon source media, such as starch, sucrose, maltose and lactose. The best carbon source then was used for further tests. Second treatment was pH media including pH of 5, 6, 7 and 8. The data obtained later were analyzed using One Way ANOVA. The selection results showed that  DG26 isolate had the best α-amylase inhibition value of 68.27% with 72 hours optimal time production. The statistical result test on the varied carbon source treatment showed insignificant effect (P> 0,05) with the best α-amylase inhibition value of 19,98% at starch treatment. The statistical result test on the varied pH treatment showed a significant different effect (P <0.05) with the best α-amylase inhibition value of 44.91% at pH 7.Keywords: α-amylase inhibitor, endophytic yeast, Tinospora crispa, carbon source, pH